Statistical Methods Used In Educational Technology Research 2012-2013 - Ritter, Nicola L. (Advances in Social Sciences Research Journal, 2020)
This article provides a content analysis of the research methodologies used in quantitative and mixed-methods articles in the top five educational technology journals between 2012 and 2013. These articles represented a total of 32,131 sampling procedures and statistical techniques recorded from 1,171 articles – the largest research synthesis of research methodologies in field of educational technology to date. Results indicate quantitative methods continue to dominate the field as a whole, yet specific journals appear to favor certain research methods over others. Most authors did not report the type of sampling procedure used in their investigations (617 articles). Fewer researchers reported score reliability estimates using their own data – with only 420 articles reporting reliability coefficients. Findings also suggest few authors reported informationally-adequate statistics. Recommendations for best statistical practices and implications for the field of educational technology are discussed.